Biodiversity enrichment in KHDTK Wanadipa forest based on agarwood plants (Auricularia malaccensis Lamk) - W Hidayat Jafron; Puryono KS Sri; Astuti Yayuk; Wibowo Pratama J. (E3S Web of Conferences)
Forests have enormous functions for life, unfortunately continue to experience a decline in quality. The condition of biodiversity also continues to be under pressure. On the other hand, Diponegoro University, Undip as a research university considers to prepare environmental concern instruments as educational forest. The aim of the research is to determine the biological richness of tree stands in Kawasan Hutan Dengan Tujuan Khusus (KHDTK). It is also to study the physical and chemical conditions, especially as a basis for vegetation enrichment with a valuable agarwood plants. The results of the study showed that the species that had great importance value in terms of seedlings and trees were Dalbergia (72%), Leucaena (44.109%) and Cassia siamea (13.199%). These species have very high reproduction rates and adaptability, since enable to produce many seeds. Indigenous forest tree, especially teak, have low important value because they have illegal logged before. There was no agarwood species or relative species found here. The soil and terrain conditions for enrichment with agarwood, are very suitable, although the slope is not really ideal. Slopes related to erosion and lead to poor soil nutrition. Alignment of planting through intercropping farming has great prospects for farmer, especially in relation to ecological and economic benefits.